High levels of TopBP1 induce ATR-dependent shut-down of rRNA transcription and nucleolar segregation. Issue 10 (27th April 2015) - Sokka, Miiko; Rilla, Kirsi; Miinalainen, Ilkka; Pospiech, Helmut; Syväoja, Juhani E.
Abstract: Nucleoli are not only organelles that produce ribosomal subunits. They are also overarching sensors of different stress conditions and they control specific nucleolar stress pathways leading to stabilization of p53. During DNA replication, ATR and its activator TopBP1 initiate DNA damage response upon DNA damage and replication stress. We found that a basal level of TopBP1 protein associates with ribosomal DNA repeat. When upregulated, TopBP1 concentrates at the ribosomal chromatin and initiates segregation of nucleolar components—the hallmark of nucleolar stress response. TopBP1-induced nucleolar segregation is coupled to shut-down of ribosomal RNA transcription in an ATR-dependent manner. Nucleolar segregation induced by TopBP1 leads to a moderate elevation of p53 protein levels and to localization of activated p53 to nucleolar caps containing TopBP1, UBF and RNA polymerase I. Our findings demonstrate that TopBP1 and ATR are able to inhibit the synthesis of rRNA and to activate nucleolar stress pathway; yet the p53-mediated cell cycle arrest is thwarted in cells expressing high levels of TopBP1. We suggest that inhibition of rRNA transcription by different stress regulators is a general mechanism for cells to initiate nucleolar stress pathway.